ESENSI DAN DAMPAK LIBERALISASI PERDAGANGAN PADA SUBSEKTOR PERKEBUNAN - WAYAN REDA SUSILA; MADE ANTARA (SOCA: Jurnal Sosial Ekonomi Pertanian, 2004)
As one of the traded goods and important sub-sectors in Indonesia, estate-crop subsectorcannot avoid various strategic business environment changes, mainly related to tradeliberalization issues. These changes have been perceived to have significant impacts on thesub-sector. In line with this issue, the main objective of this paper is to assess the likelyimpacts of trade liberalization with emphasizing on the Indonesian estate crops sub-sector.The results of the study indicates that impacts of the trade liberalization on the subsectorin the international markets have been varied, due to the different level of marketdistortions, level of commitments to reduce distortion, and consistency in implementing thecommitments. In general, trade liberalization is expected to lift international prices, while theimpacts on production, consumption, and trade have been varied, depending on the crops andcountries. Moreover, Indonesia estate crops sub-sector will benefit from this tradeliberalization if some conditions to promote efficiency and to fair trade in international marketcould be realized.